Peningkatan Daya Saing Objek Wisata Berbasis Komunitas Melalui Pemanfaatan Social Media Marketing dan Analisis Akuntansi Perpajakan di Desa Bongkasa Provinsi Bali - I Wayan Chandra Adyatma; I Putu Gede Satria Wiraharja; I Made Dwi Sumba Wirawan (Institut Teknologi dan Bisnis Semarang, 2023)
Tourism Village is one of the popular forms of tourist destinations developed in the Bali Province. Bongkasa Tourism Village, located in the Abiansemal District of Badung Regency, generates income from small and medium-sized businesses, villa accommodations, restaurants, and cafes. There are two main issues in the development of the community-based tourism village in Bongkasa Village, Badung Regency: 1. The underutilization of social media and digital marketing in promoting tourist attractions in Bongkasa Village, Badung Regency. 2. Some tourism-related businesses in Bongkasa Village are not operating professionally, lacking proper accounting and tax compliance for their operations.To address these issues, community engagement is necessary with the tourism-aware group in Bongkasa Village, focusing on the theme of